La juegoteca como elemento potencializador para el desarrollo intelectual, social, emocional y físico de los niños de nivel inicial de la Unidad Educativa José Domingo de Santisteván - Larriva Obregón, María Fernanda (2012)
The purpose of this investigative project, is to achieve that the counselors, teachers and parents of the Unidad Educativa Santiestevan, cociencize the importance of the games in the kids, because is a natural form to explore the world, and to learn to live, to know itselfs, others and nature, the same that makes them express what they feel, and solve the little problems that they have, transform reality with the imagination, and enhance physical, intellectual, emotional, and social capabilities also it will enrich their communication with an integral and spontaneous form. From the notion of the games we learn the concept of toy library, this are design spaces for the ludic expression, equipped with the necessary resources, that can be transformed with the imagination and the creativity of the pupil, this space is optimal for the spontaneous creativity of different classes of games, emerges as device with the open and own knowledge, versatile and creative, as a result of post-modernity and global paradigm shift…….